Performance Evaluation of Two Port and Four Port Measurement for Twisted Pair Cable - Azhari Bin Asrokin; Mohamad Kamal Bin A. Rahim (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A balance-unbalance (balun) transformer is commonly used to connect the balance 100 Ohm twisted pair cable to the unbalance 50 Ohm network analyzer ports, but due to the limitations of the core (i.e. ferrite) inside the balun, the balun can only effectively operates at a certain band of frequencies. This limitation can be eliminated by using a 4-port vector network analyzer (VNA) which is done by connecting the VNA’s ports to each conductor end. The extracted S-parameters will then be transformed to a 2-port S-parameters in differential mode at both ports. To validate the measurement technique, S-parameter measurement by using the 4-Port Network Analyzer without any balun will be compared to the measurement which used the 2-Port Network Analyzer with the balun transformers. Two twisted pair cable distances are selected as reference which are 500, and 1000 meters with nominal copper diameter of 0.5mm. Based on the measurement results, the 4-ports measurement shows good correlation with the 2-ports measurement especially at 500m distance. This shows that the 4-ports measurement setup is suitable to be used to measure twisted pair copper cable and possible to measure at a higher frequency band such as up to 500 MHz but at a shorter twisted pair cable distance.